2020
DOI: 10.1093/biolre/ioaa049
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease inhibitor disrupts sperm motility leading to reduced fertility in female mice†

Abstract: Inhibition of the sperm transport process in the female reproductive tract could lead to infertility. We previously showed that a pan-serine protease inhibitor, 4-(2-aminoethyl)benzenesulfonyl fluoride (AEBSF), blocked semen liquefaction in vivo and resulted in a drastic decrease in the number of sperm in the oviduct of female mice. In this study, we used a mouse model to test the efficacy of AEBSF as a reversible contraceptive, a sperm motility inhibitor, and a spermicide. Additionally, this study evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…The entire mount oviduct was used for transcriptomic analysis since there is a potential interaction between the stromal cells and epithelial cells 25 . In Tgfbr2 cKO mice, the upregulation of Has1 and the downregulation of Cemip may prevent sperm migration in the oviduct by increasing hyaluronan levels 37 , and the upregulation of Serpina1e may impair the spermatozoa motility by inhibiting serine proteases 38 . The activation of cell adhesion and NF-kappa B signaling in the oviductal cells of Tgfbr2 cKO mice may impair spermatozoa moving out of the isthmic reservoir 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The entire mount oviduct was used for transcriptomic analysis since there is a potential interaction between the stromal cells and epithelial cells 25 . In Tgfbr2 cKO mice, the upregulation of Has1 and the downregulation of Cemip may prevent sperm migration in the oviduct by increasing hyaluronan levels 37 , and the upregulation of Serpina1e may impair the spermatozoa motility by inhibiting serine proteases 38 . The activation of cell adhesion and NF-kappa B signaling in the oviductal cells of Tgfbr2 cKO mice may impair spermatozoa moving out of the isthmic reservoir 39 .…”
Section: Discussionmentioning
confidence: 99%
“…And then, motile and non-motile sperm were counted under a dark-field microscope to determine sperm concentration and motility. For more sophisticated and automated analysis, sperm samples were incubated at 37 • C for 15 min and analyzed using computer-assisted sperm analysis (CASA) (SCA CASA system; Fertility Technology Resources, Inc.) following the manufacturer's instructions as previously described [14,15].…”
Section: Sperm Analysismentioning
confidence: 99%
“…Pan-serine protease inhibitor, 4-(2aminoethyl)benzenesulfonyl fluoride (AEBSF) shown in Scheme 1, [88] has also been shown to negatively affect sperm motility and viability at millimolar concentrations, in a mouse model of contraception. [89] However, in vitro toxicity testing also demonstrated that at doses of 1 and 5 mM, AEBSF significantly decreased human ectocervical cell (ECT) viability. Consequently, a small fragment-like molecule with a covalent warhead, may interact with many different proteins and both the contraceptive and toxic effects observed may be due to the inhibition of multiple protein targets.…”
Section: Serine Proteasesmentioning
confidence: 99%